Spatial variability of soil pH and electrical conductivity in the Jammu district of Jammu and Kashmir - SHARMA, VIKAS; ARYA, VIVAK M.; SHARMA, K. R. (Journal of Soil and Water Conservation, 2020)
A study was conducted to assess the spatial variability of pH and EC of Jammu district soils and generate their prediction maps. The Jammu district of Jammu and Kashmir covers an area of 2336 sq. km. and falls in the sub-tropical zone of the state. The district has two very distinct regions, the southern irrigated plains and northern rainfed foothills. Soil samples were collected from the entire Jammu district following the stratified random manner. A semi-variance analysis was conducted to estimate nugget, sill and range for quantifying the spatial dependence for both pH and EC. The process of digitization and generation of maps was carried out with ArcGIS 9.2 software following ordinary kriging. Soil pH varied widely across the Jammu district ranging from as low as 4.67 to as high as 9.08 with a mean value of 7.07. The coefficient of variation (CV) was 9.85 %. Nugget to sill ratio was 0.396 (39.6%), indicating moderate spatial variability. The range of spatial dependence was 32.3 km. Electrical Conductivity (EC) ranged from 0.021 to 1.523 dS m-1 with a mean value of 0.225 dS m-1. The EC had a high variability with a CV (coefficient of variation) value of 79.94 %. It’s range of spatial dependence was 32.93 km. EC also exhibited a moderate spatial variability with a nugget to sill ratio of 0.478 (47.8%). Both pH and EC increased towards the southern plains of the district. Topography and associated land use/land cover played a major role in the distribution of pH and EC.